Cutaneous lichen planus: A systematic review of treatments. (June 2015) - Fazel, Nasim
Abstract Various treatment modalities are available for cutaneous lichen planus. Pubmed, EMBASE, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, Database of Abstracts of Reviews of Effects, and Health Technology Assessment Database were searched for all the systematic reviews and randomized controlled trials related to cutaneous lichen planus. Two systematic reviews and nine relevant randomized controlled trials were identified. Acitretin, griseofulvin, hydroxychloroquine and narrow band ultraviolet B are demonstrated to be effective in the treatment of cutaneous lichen planus. Sulfasalazine is effective, but has an unfavorable safety profile. KH1060, a vitamin D analogue, is not beneficial in the management of cutaneous lichen planus. Evidence from large scale randomized trials demonstrating the safety and efficacy for many other treatment modalities used to treat cutaneous lichen planus is simply not available.